Chronic low-dose pro-oxidant treatment stimulates transcriptional activity of telomeric retroelements and increases telomere length in Drosophila - Korandová, Michala; Krůček, Tomáš; Szakosová, Klára; Kodrík, Dalibor; Kühnlein, Ronald P; Tomášková, Jindřiška; Čapková Frydrychová, Radmila (Journal of insect physiology, 2018)
It has been proposed that oxidative stress, elicited by high levels of reactive oxygen species, accelerates telomere shortening by erosion of telomeric DNA repeats. While most eukaryotes counteract telomere shortening by telomerase-driven addition of these repeats, telomeric loss in Drosophila is compensated by retrotransposition of the telomeric retroelements HeT-A, TART and TAHRE to chromosome ends. In this study we tested the effect of chronic exposure of flies to non-/sub-lethal doses of paraquat, which is a redox cycling compound widely used to induce oxidative stress in various experimental paradigms including telomere length analyses. Indeed, chronic paraquat exposure for five generations resulted in elevated transcriptional activity of both telomeric and non-telomeric transposable elements, and extended telomeric length in the tested fly lines. We propose that low oxidative stress leads to increased telomere length within Drosophila populations. For a mechanistic understanding of the observed phenomenon we discuss two scenarios: adaption, acting through a direct stimulation of telomere extension, or positive selection favoring individuals with longer telomeres within the population.
Keywords: Telomere; Reactive Oxygen Species; zvířata; Drosophila melanogaster; telomery; genetická transkripce; Dose-Response Relationship, Drug; zkracování telomer; Animals; reaktivní formy kyslíku; paraquat; Telomere Shortening; Hormesis; Retroelements; Paraquat; homeostáza telomer; retroelementy; hormeze; vztah mezi dávkou a účinkem léčiva; Telomere Homeostasis; Transcription, Genetic